Субоцький печерний монастир / Cave monastery in Subich (Middle Dniester - Рідуш, Богдан; Нечитайло, Павло (Чернівецький національний університет імені Юрія Федьковича, кафедра етнології, античної та середньовічної історії, 1999)
The article describes Subich Monastery (Kamianets'-Podil'sky District of Khmelnysky Region), one of the monasteries in the Middle Dniester. It gives a brief description of the petroglyphic Christian images and inscriptions-graffiti on the cave walls. In comparison with the other Christian cave monuments in Bulgaria and Romania, the time of the monastery's founding is referred to as the 14th century.